Front-induced transitions - Gaafar, Mahmoud A.; Baba, Toshihiko; Eich, Manfred; Petrov, Alexander Yu (Nature photonics, 2019)
Refractive index fronts propagating in waveguides are special spatiotemporal perturbations. The interaction of light with such fronts can be described in terms of an indirect transition where the frequency and wavenumber of a guided mode both are changed. In recent years, front-induced transitions have been used in dispersion-engineered waveguides for frequency conversion, optical delays, and bandwidth and pulse duration manipulation. These concepts have originated from different research areas of photonics, such as nonlinear fibre optics, slow-light waveguides, plasma physics, moving media and relativistic effects. Here, we discuss these concepts, providing a unifying theoretical description and highlight the potential of this exciting research field for light manipulation in guided optics. Front-induced transitions have been used in dispersion-engineered waveguides for frequency conversion, optical delays, and bandwidth and pulse duration manipulation. This Review provides a theoretical description of the subject and highlights the potential for light manipulation in guided optics.